Factors associated with low birth weight: a case-control study - Getial Mora, Daniela Alejandra; Aguirre Contreras , Leidys Paola; Afanador Cataño, Maritza; Tocora Rodríguez, Juan Camilo (Revista Cuidarte, 2026)
Highlights • Pregnant women residing in rural areas presented a higher risk of low birth weight, reflecting geographical inequalities in maternal and neonatal health. • Hospitalization during pregnancy was identified as the factor most strongly associated with low birth weight in the studied population. • The female sex of the newborn showed a significant association with low birth weight, which coincides with biological patterns observed in other populations. • Previous reproductive system surgery acted as a protective factor, possibly due to longer obstetric follow-up and intensified prenatal care. Introduction: Term low birth weight is a multifactorial event influenced by maternal, fetal, and socio-environmental conditions. Understanding it enables the design of targeted preventive interventions. Objective: To analyze the factors associated with low birth weight in term newborns attended at a tertiary-level clinic in Córdoba between 2020 and 2023. Materials and Methods: A retrospective case–control study. The sample size was calculated with 80% power and a 95% confidence level. A total of 84 cases and 169 controls were included through stratified random sampling. Maternal clinical and sociodemographic variables were analyzed using multivariate logistic regression. Results: Low birth weight was associated with hospitalization during pregnancy (aOR = 6.05; 95% CI: 2.94–12.47), rural residence (aOR = 2.65; 95% CI: 1.21–5.81), and female sex of the newborn (aOR = 1.97; 95% CI: 1.07–3.64). Maternal reproductive tract surgery acted as a protective factor (aOR = 0.37; 95% CI: 0.20–0.71). Discussion: The findings highlight the combined influence of clinical and social factors, particularly gestational hospitalization and rural residence, conditions that may limit timely prenatal care and increase perinatal risk. Conclusion: Preventing low birth weight requires strengthening the quality of prenatal care, prioritizing follow-up for pregnant women with prior hospitalization, and establishing differentiated care pathways for rural women to improve access and ensure timely maternal–fetal care. How to cite this article: Getial Mora Daniela Alejandra, Aguirre Contreras Leidys Paola, Afanador Cataño Maritza, Tocora Rodríguez Juan Camilo. Factors associated with low birth weight: a case-control study. Revista Cuidarte. 2026;17(2):e5511. https://doi.org/10.15649/cuidarte.5511